2014
DOI: 10.1016/j.jcat.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Gold catalysts for the synthesis of aromatic azocompounds from nitroaromatics in one step

Abstract: One step selective hydrogenation of nitroaromatics to obtain symmetric azocompounds with high yields has been performed with a gold supported on cerium oxide catalysts. Au/TiO 2 and Au/CeO 2 catalysts direct the reaction by two different pathways and with different selectivities. In situ FTIR studies reveal that the surface concentration of the intermediate nitrosobenzene is decisive in directing the reaction trough the different reaction pathways. In this way, while on Au/TiO 2 a fast hydrogenation of the nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 18 publications
6
83
0
1
Order By: Relevance
“…Thus, Corma et al. have demonstrated that the reaction proceeds through the direct route if it is catalyzed by Au‐TiO 2 , and Noschese et al. showed that the condensation route seems to prevail if the AuNPs are supported onto a nanoporous polymeric matrix .…”
Section: Resultssupporting
confidence: 56%
“…Thus, Corma et al. have demonstrated that the reaction proceeds through the direct route if it is catalyzed by Au‐TiO 2 , and Noschese et al. showed that the condensation route seems to prevail if the AuNPs are supported onto a nanoporous polymeric matrix .…”
Section: Resultssupporting
confidence: 56%
“…The course of the reaction depends on the experimental conditions, namely the metal catalyst, the temperature, the reductant and the nitroaromatic/reductant molar ratio. In two elegant papers Corma et al demonstrated that NB reduction catalyzed by Au-TiO 2 in the presence of H 2 proceeds through the direct route involving the phenylhydroxylamine intermediate (Scheme 1b) [6b,36]. The FTIR monitoring of the reaction showed that at low coverage degree of the AuNPs surface, nitrosobenzene is rapidly transformed into phenylhydroxylamine and then into AN; the latter reaction is commonly considered the rate determining step.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…[12] Thanks to the discovery that supported gold nanoparticles (NPs) are capable of uniquely facilitating the direct nitronitroso-hydroxylamine pathway, it is now possible for targetspecific synthesis of substituted anilines and related derivatives by using catalytic nitro-group hydrogenation in a highly regio-and chemoselective manner. [15] In view of the likely intermediacy of the azo compound in the selective hydrogenation of nitroarenes, and considering that the selectivity of the nitro reduction might be tuned in favor of azo products by rational regulation of the synergy between the metal and support in the gold catalyst system, we were motivated to explore gold deposited on functional support with tailored surface redox and acid-base properties as a catalyst for the direct hydrogenative coupling of nitro compounds. [14] One major limitation of this procedure, however, is that it is potentially dangerous when applied to large-scale commercial applications.…”
mentioning
confidence: 99%